The enhanced association between mutant CHMP2B and spastin is a novel pathological link between frontotemporal dementia and hereditary spastic paraplegias. - Chen, Y.; Krishnan, G.; Parsi, S.; Pons, M.; Nikolaki, V.; Cao, L.; Xu, Z.; Gao, F.B. (Acta neuropathologica communications, 2022)
Chromosome 3-linked frontotemporal dementia (FTD3) is caused by a gain-of-function mutation in CHMP2B, resulting in the production of a truncated toxic protein, CHMP2BIntron5. Loss-of-function mutations in spastin are the most common genetic cause of hereditary spastic paraplegias (HSP). How these proteins might interact with each other to drive pathology remains to be explored. Here we found that spastin binds with greater affinity to CHMP2BIntron5 than to CHMP2BWT and colocalizes with CHMP2BIntron5 in p62-positive aggregates. In cultured cells expressing CHMP2BIntron5, spastin level in the cytoplasmic soluble fraction is decreased while insoluble spastin level is increased. These pathological features of spastin are validated in brain neurons of a mouse model of FTD3. Moreover, genetic knockdown of spastin enhances CHMP2BIntron5 toxicity in a Drosophila model of FTD3, indicating the functional significance of their association. Thus, our study reveals that the enhanced association between mutant CHMP2B and spastin represents a novel potential pathological link between FTD3 and HSP.